The Development of a Training Curriculum on Teacher Competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension for Primary School Teachers under Surin Primary Educational Service Area Office 3 - Chaikhirin, Natnicha; Jantachum, Nattachai; Sujaree, Tipaporn (Journal for Developing the Social and Community, 2026)
Background and Aims: This research aimed to: 1) study the current state and the desired state, and the needs with regard to teacher competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension, 2) develop a training curriculum for teachers' competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension, 3) implement the training curriculum for teachers' competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension and 4)evaluate the training curriculum for teachers' competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension. Methodology: The research was conducted in four phases: Phase 1: fundamental data study; Phase 2: training curriculum development; Phase 3: training curriculum implementation; and Phase 4: training curriculum evaluation. A target group was 30 primary English teachers from schools under the Surin Primary Educational Service Area Office 3, selected by purposive sampling through voluntary participation with school administrator cooperation. Research tools were training curriculum, tests, assessment forms, competency measurement tools, and training curriculum evaluation forms. Statistics used for data analysis include percentage, mean, standard deviation, and t-test (Dependent Samples). Results: 1. Teacher competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension of 3 domains, 10 competencies, and 33 indicators as follows: 1) Knowledge domain with 5 competencies and 19 indicators, 2) Skills domain with 4 competencies and 10 indicators, and 3) Attitude domain with 1 competency and 4 indicators. The study of the current state and the desired state, and needs regarding teacher competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension that the current state of teacher competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension. was overall at a low level ( = 1.95, S.D. = 0.37). The desired state of teacher competencies in Content and Language Integrated Learning (CLIL) for English Reading Comprehension was overall at a high level ( = 4.87, S.D. = 0.03), and teachers demonstrated a need for development in all competencies with regard to Content and Language Integrated Learning (CLIL) for English Reading Comprehension. 2. The training curriculum for teacher competencies Content and Language Integrated Learning (CLIL) for English Reading Comprehension consisted of 6 components: 1) Principles, 2) Objectives, 3) Content, 4) Learning activities, 5) Media, innovations, and learning resources and 6) Measurement and evaluation. The content consisted of 5 learning units totaling 24 hours: Unit 1 - Covering fundamental CLIL knowledge (3 hours), Unit 2 - principles of developing English reading comprehension through CLIL (6 hours), Unit 3 - Media and innovations (6 hours), Unit 4 - Lesson plan design (6 hours) and Unit 5 - Lesson plan presentation (6 hours). Learning activities were designed based on experiential learning, cooperative learning, social constructivism, learning by doing, and presentation. 3. The results of the curriculum implementation indicated that teachers’ knowledge competency after training was significantly higher than before training at the .01 level of statistical significance. Teachers’ skills competency was at a high level ( = 4.55, S.D. = 0.55). Overall attitude competencies were at a high level ( = 4.80, S.D. = 0.11), with post-training attitudes higher than pre-training attitudes. Overall satisfaction with the training curriculum was at the highest level ( = 4.52, S.D. = 0.51) 4. The evaluation results of the training curriculum showed that the overall was at the highest level ( = 4.60, S.D. = 0.21). Conclusion: The developed training curriculum is consistent with the identified needs and effectively enhances teachers' competence in Content and Language Integrated Learning (CLIL) for improving English reading comprehension. It has the potential for further application and development.